BUDGET EFFICIENCY AS A DETERMINANT OF EMPLOYEE PERFORMANCE WITH LEADERSHIP AND JOB SATISFACTION AS SUPPORTING VARIABLES IN THE DEPARTMENT OF FOOD SECURITY AND AGRICULTURE OF CILEGON CITY - Maryori Maryori; Ahmad Mukhlis; Mamay Komarudin (Yayasan Education and Social Center, 2026)
This study aims to analyze the influence of leadership and job satisfaction on budget efficiency through employee performance at the Food Security, Agriculture, and Fisheries Agency of Cilegon City. The study used a quantitative approach with a survey method. The study population consisted of 93 employees consisting of Civil Servants (PNS) and Government Employees with Work Agreements (PPPK). The sampling technique used saturated sampling (census sampling), so that the entire population became respondents. Data were collected through questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0 software. The results showed that leadership had a positive and significant effect on budget efficiency and employee performance. Job satisfaction was also proven to have a positive and significant effect on budget efficiency and employee performance. In addition, employee performance had a positive and significant effect on budget efficiency. Testing the mediation effect proved that employee performance was able to significantly mediate the influence of leadership and job satisfaction on budget efficiency. Research findings confirm that improving budget efficiency in public sector organizations is not solely determined by financial management, but is also influenced by leadership quality, job satisfaction, and employee performance. Therefore, strengthening leadership capacity, improving employee welfare, and developing human resource competencies are crucial strategies for achieving effective, efficient, and performance-oriented organizational governance.